A novel dynamic replica creation mechanism for Data Grids - Madi, Mohammed Kamel; Mohamad Tahir, Hatim; Yusof, Yuhanis; Hassan, Suhaidi (2015)
The abstract Data Grid is an infrastructure that manages huge amount of data files, and provides intensive computational resources across geographically distributed collaboration.A key concept in Data Grids is replication of data, whereby multiple copies of data are stored at different geographical locations, making access to data faster and more reliable.However, replication is also bounded by two factors: the size of storage available at different sites within the Data Grid and the bandwidth between these sites. In this paper, we proposed a dynamic replication mechanism termed as Replica Number Mechanism (RNM) that determine the optimal number of replicas to be created or deleted with the aim of minimizing the overall resource usage (network bandwidth and storage usage).OptorSim is used to evaluate the performance of the proposed mechanism. The simulation results show that RNM requires less execution time and consumes less network usage and storage usage compared to existing approaches of Simple Optimizer and LFU (Least Frequently Used).